Experimental study of a compartmented fluidized bed gasifier for fuel gas production from oil palm shell biomass - Chok, Vui Soon (Curtin University, 2011)
Both experimental study of pilot plant scale cold flow model and pilot plant performance testing were carried out in this research with particular reference to palm shell as a biomass feedstock. The reactor was based on the concept of compartmented fluidized bed gasifier (CFBG). Sand was used as second fluidizing material.From the cold flow model, the single component (sand) system characteristic fluidization velocities for the gasifier are larger than those observed in the combustor. These differences can be minimized by utilizing larger sand size. The existing correlations are modified for the sand. For the binary mixture, the characteristic fluidization velocities showed the tendency to increase with the increase in the palm shell size and weight percent. The concept of critical loading is introduced to characterize the palm shell content in the binary mixture where the characteristic fluidization velocities for the binary mixture are determined principally by the sand. The critical loading increases with the sand size, but decreases with the increase of palm shell size. The correlations developed for the sand can be used for the binary mixture within the critical loading.Despite of the local variation on the palm shell vertical and lateral distribution, the overall good mixing quality can be established in both the compartments. The overall mixing quality is enhanced with the decrease in the palm shell size and the increase in the palm shell weight percent. Bigger bed diameter also improves the overall mixing quality while bed height did not contribute significantly.Solid circulation rate (SCR) increases with the increase in the bed height while the main bed aeration does not affect the SCR. Based on statistical approach, the V-valve and riser aerations are simultaneously adjusted to determine the optimum SCR. Optimum SCR value increases with the increase in the sand size.The pilot plant designed by using the findings from the cold flow model has demonstrated CFBG as a prospective technology for palm shell gasification for the production of medium calorific value fuel gas. The conceptual model of the palm shell gasification process was proposed.